PENGARUH BUDAYA ORGANISASI, KEADILAN ORGANISASIONAL, DAN MOTIVASI KERJA TERHADAP KOMITMEN ORGANISASIONAL - Pratiwi, Komang Ririn Sindia; Dewi, I Gusti Ayu Manuati (E-Jurnal Manajemen, 2020)
The purpose of this study is to explain the influence of organizational culture, organizational justice, and work motivation on organizational commitment. The population in this study amounted to 133 employees of CV. Tirta Tamanbali. This research was conducted on employees of CV. Tirta Tamanbali used as a research sample. The sample size taken was 100 respondents with the simple random sampling method. Data collection methods in this study were conducted by interview and questionnaire. The analysis technique used is multiple linear regression analysis. The results showed that organizational culture, organizational justice, and work motivation had positive and significant effects on organizational commitment. The results of this study can enrich social exchange theory (social exchange theory) and are expected to provide knowledge about the influence of organizational culture, organizational justice, and work motivation on organizational commitment. This research is expected to make a positive contribution to the CV. Tirta Tamanbali to increase employee organizational commitment. Keywords: organizational commitment, organizational culture, organizational justice, work motivation